Prediction of Adaptive Self-Regulatory Responses to Arthritis Pain Anxiety in Exercising Adults: Does Pain Acceptance Matter? - Miranda A Cary; Nancy C Gyurcsik; Lawrence R Brawley (Pain Research and Management)
BACKGROUND: Exercising for ≥150 min/week is a recommended strategy for self-managing arthritis. However, exercise nonadherence is a problem. Arthritis pain anxiety may interfere with regular exercise. According to the fear-avoidance model, individuals may confront their pain anxiety by using adaptive self-regulatory responses (eg, changing exercise type or duration). Furthermore, the anxiety-self-regulatory responses relationship may vary as a function of individuals’ pain acceptance levels.